2018
DOI: 10.1155/2018/7358472
|View full text |Cite
|
Sign up to set email alerts
|

The Venom of Spectacled Cobra (Elapidae:Naja naja):In VitroStudy from Distinct Geographical Origins in Sri Lanka

Abstract: Several countries residing envenomation due to Naja naja had revealed a disparity in the venom composition according to their geographic location and Sri Lankan cobra still lacks the evidence to support this. Therefore, the current study was focused on addressing relationship between the histopathological changes according to geographic variation of Sri Lankan N. naja venom. The histopathological changes in vital organs and muscle tissues following intramuscular administration of venom of N. naja were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Increasing evidence suggests a sizable involvement of hemotoxins in the morbidity associated with N.N bite, causing wide-spread changes in hemostasis. These effects are mediated by toxins that affect platelet aggregation (Kumar et al, 2010), coagulation (Berling and Isbister, 2015), hemolysis (Dissanayake et al, 2018) and fibrinogenolysis (Gowda et al, 2006;Kumar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests a sizable involvement of hemotoxins in the morbidity associated with N.N bite, causing wide-spread changes in hemostasis. These effects are mediated by toxins that affect platelet aggregation (Kumar et al, 2010), coagulation (Berling and Isbister, 2015), hemolysis (Dissanayake et al, 2018) and fibrinogenolysis (Gowda et al, 2006;Kumar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cobra venom cardiotoxins (CVCs) have been used as a molecular tool to probe the structure and functions of biological membranes [20,21] by studying the structure of model membranes [22,23,24]. Importantly, CVCs have also been investigated as potential therapeutic agents to treat various diseases, including cancer [20,21,25,26,27]. Recently, CVCs have been described as potential therapeutic agents to restore mitochondrial bioenergetics in age-associated neurodegenerative diseases [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies in geographical variations involving envenomation by N. naja revealed that the median lethal dose in mice differed between northern (0.55 mg/ kg), central (0.66), western (0.68), southern (0.62) and Sabaragamuwa (0.7) regions respectively. Histopathological changes of these regional venoms, however, showed a higher affinity for certain bodily systems, with northern venom observing a significantly higher infiltration of inflammatory and necrotic cells into skeletal muscle and central venom demonstrating high cardiotoxic effects, these results confirm venom disparity [74]. Geographical location showed a remarkable degree of variation amongst Bitis arietans species originating from the same geographical origin, most evident by the venom components metalloproteinases [71].…”
Section: The Geographical Variations In Snake Venommentioning
confidence: 71%